Lendas urbanas: atualização, persistência e "realidade" nessas narrativas multimídia - Moreira, Natália Eunice Paiva (2010)
This research processes and analyzes the popular contemporary narratives that are told in Brazil. The material was collected through bibliographical researches and interviews. This work aims to explain how the urban legend phenomenon is constituted of media production and historical and cultural environment, plus social, political and cultural mediations and impacts over daily life. The urban legend in this work is seen as an actualization of tradition, which is build in a mobile cultural network that involves orality and multiple media supports (such as newspaper, internet, mobile phone). This creative network reveals anxieties, interdictions, fears and prescriptions of a determined society in a determined place. The main references of this research are the contemporary legend studies, such as Paul Smith, Gillian Bennet, Jean-Bruno Renard, Jean-Nöel Kapferer, Véronique Campion-Vincent; the ideia of mythpoetics found in the work of Eleazar Meletinski; the cultural studies of Jerusa Pires Ferreira and Jesus Martin-Barbero; the idea of semiosphere, from Iuri Lotman. The collected material is analyzed in its internal and external aspects. The goal is to understand how each urban legend is constituted and how it operates in determined society and place